ANALISIS PRODUK KREATIF BERBASIS UP CYCLE DALAM MENINGKATKAN KREATIVITAS SENI DAN KEMAMPUAN MENULIS SISWA KELAS V SD - Rini Esti Rahayu; Moh Rusnoto; Siti Rochmiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Increase student creativity with waste recycling creations at SDN 1 Wonokerso. This research is motivated by the incident where children in this era will easily get anything they want, and the fear in following the learning as a result they will tend to be lazy to do things that they consider complicated and difficult to get. They will also be passive students and students, able only to accept the lesson without understanding what is being taught. Many negative things can arise from this incident. The purpose of this study was to find out whether there is an increase in creativity and writing skills of students carried out by recycling recycling activities. The method used is a qualitative research method with a descriptive qualitative approach. by using the rubric of practice and assessment as a reference assessment given to see if there is an increase in creativity in making waste recycling creations. The researcher hopes that the research conducted by the researcher can be useful for many people.